Ionospheric propagation of magnetohydrodynamic disturbances from the equatorial electrojet - Fedorov, E.; Pilipenko, V.; Surkov, V.; Rao, D. R. K.; Yumoto, K. (My University, 1999)
The propagation features of magnetohydrodynamic (MHD) disturbances along the ionosphere are considered from a theoretical point of view. Special attention is paid to the possibility of ionospheric propagation of disturbances produced by variations in the equatorial electrojet. The possible MHD modes within the E layer include oscillations that have damping scales of about effective ionospheric skin depth or less. The existence of a large-scale compressional surface mode at small inclinations of the geomagnetic field along the E layer is shown. The propagation of this mode, called the gyrotropic surface mode, takes place in a diffusive-like way along the E layer. Its damping scale is much greater than the ionospheric skin depth, and it may reach several hundred to thousand kilometers. The apparent propagation velocity of the gyrotropic mode at the near-equatorial latitudes is determined by height-integrated Cowling conductivity; its value is estimated to be about 20 – 100 km/s for the Pc3–4 frequency range. We suggest that the equatorial electrojet may contribute to the ULF geomagnetic variations observed at near-equatorial stations.
Keywords: Ionospheric propagation; Magnetohydrodynamic; Equatorial electrojet; E layer; Geomagnetic variations